MACHINE LEARNING MODEL FOR CORROSION PREDICTION: CASE STUDY ON SABAH OIL AND GAS TERMINAL (SOGT) - Zuraimi, Muhammad Zur Faiezzuddin (IRC, 2019)
The Sabah Oil and Gas Terminal (SOGT) is a part of the Sabah-Sarawak Integrated Oil and Gas Project (SSIOGP) undertaken by Petronas Carigali in the state of Sabah (PCSB SBA), in east Malaysia. The terminal processes oil and gas produced from the region’s offshore fields. PCSB SBA is operating 4 incoming trunk lines (18” GOP, 14” KOP & 24” KNNAG) to SOGT. 24” gas pipeline is operated by KPOC. All these trunk lines are currently transporting maximum throughput capacity which bring highest revenue to PETRONAS as show in Figure 1. Currently PCSB SBA is commissioning a Pipeline Management System (PMS) as part of SOGT project deliverables for all the 4 incoming trunk lines.